Corpus callosotomy for treatment of pediatric epilepsy: two clinical cases and a literature review - Matonytė , R.; Ročka , S.; Grikinienė , J. (Neurologijos seminarai, 2020)
Epilepsy is one of the most common chronic diseases in children and it affects approximately 6.1 per 1000 children in Lithuania as of 2018 data. The onset of epilepsy most often develops in children and older adults. The condition of epilepsy may be traced to various factors and seizure symptoms can vary widely. Controlled seizures are the main goal of epilepsy management. Children with uncontrolled seizures may develop speech, language, cognitive and behavioral dysfunction epileptic encephalopathies. Effective management of epilepsy in children not only improves condition of health, but also reduces social exclusion and helps integrate into educational activities. However, even if the disease is diagnosed early and appropriate antiepileptic drug therapy is prescribed, epileptic seizures persist in 20-40% of patients. For some of these patients, surgical treatment of epilepsy, such as resection or palliative surgery, may be effective in reducing seizures. Resection of a localized epileptogenic focus is an effective treatment for appropriate refractory cases. However, not all patients are candidates for the resection, for example, in the case of multifocal or rapidly generalizing seizures without a clearly identified epileptogenic focus. One of the most effective treatment for refractory epilepsy is corpus callosotomy. The corpus callosum is the most important pathway for the spread of epileptic activity between the two hemispheres of the brain. Its cutting precludes epileptic discharges from traveling between hemispheres (i.e., generalization). Overall, long-term follow-up studies after callosotomy have shown improvement in 80-90% of patients (seizure-free or reduction). The paper describes two pediatric patients treated in Vilnius University Hospital Santara Clinics, Department of Pediatric Neurology and Neurosurgery, who underwent a corpus callosotomy, and compares the outcome of these clinical cases with the results of recent clinical trials.